Effect of adsorbate initial concentration on the removal of Pb from aqueous solutions by carbon nanofibers - Ahmed, Yehya M.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Al-Khatib, Ma An Fahmi Rashid; Jameel, Ahmed Tariq; Al-Saadi, Mohammed A. (2010)
The effect of lead (Pb) initial concentration on the adsorption of the heavy metal from aqueous solutions by using carbon nanofibers (CNFs) was studied. The isotherm of the sorption of the heavy metal onto the nanocomposite was also studied. The effects of initial lead ions concentration were examined and the results showed that the residual concentration of the heavy metal after adsorption by the carbon nanofibers was increased from 0.5 to about 37 with increasing the initial lead concentration from 5 to 70 mg/L. Highest removal of Pb ions was achieved at metal initial concentration of 5 mg/L (89%). The process sorption could be best fitted by the Langmuir isotherm. The equilibrium sorption capacity of lead ion were determined and found to be 132 mg/ g at initial concentration of 70 mg/L.